Systematic Literatur Review (SLR) : Analisis Problematika Mahasiswa Pendidikan Matematika Pada Mata Kuliah Analisis Real - Tasya Aulia Faisal; Rusi Ulfa Hasanah; Rindi Fatmawati (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study was to analyze the problems of mathematics education students in real analysis courses. This research uses the Systematic Literature Review (SLR) method. The research objective of the Systematic Literature Review (SLR) method is to evaluate, review and recognize relevant research so as to be able to answer questions on the specified research. The results of the research from analyzing this that the most common problem faced is the occurrence of student misconceptions about the material, concepts in learning that are quite a lot, minimal Indonesian language sources, still less able to construct mathematical evidence and internal factors are lack of interest and motivation in learning so that it seems difficult..